Strategi Penerapan Layanan bimbingan dan Konseling Karir Pada Sekolah Menegah Atas Berbasis Islam Di Kurikulum Merdeka - Marsal Yunas muliadi; Tri Putri Amelia; Masril Masril (Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2023)
This research originates from the phenomenon of guidance and counseling teachers who experience problems with suitable techniques in implementing career guidance and counseling in schools. The aim of the research is to describe the strategy for implementing career guidance and counseling in senior high schools in the independent curriculum. Methods in research using qualitative. The instrument in this study was the researcher as the key, then the informants in the research were guidance and counseling teachers. Data processing techniques in this study used data reduction, data display, and drawing conclusions. Testing the validity of the data using triangulation from sources. KEYWORDS: Strategy, guidance and counseling, career, independent curriculum